2016
DOI: 10.1371/journal.pone.0167565
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Improvement among HIV Infected Pre-School Children Following Initiation of First Line Anti-Retroviral Therapy: Implications for Follow Up

Abstract: BackgroundAntiretroviral therapy (ART) is a lifesaving intervention for HIV infected children. There is a scarcity of data on immunological recovery and its relation with growth indicators among HIV infected young children. The current study aims to assess the pattern of anthropometric Z-score improvement following initiation of first-line ART among under-five children and the relationship between anthropometric Z-score improvement and immunologic recovery.MethodsWe included under-five children who were on fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…Although notably, as found in our study, Canadian CWH in early puberty had higher cortical BMD compared with CWOH. (38) An extensive literature has established a higher prevalence of stunting and underweight in CWH than in CWOH, (4,5,(39)(40)(41)(42) which has been confirmed by our study and our earlier studies in Zimbabwean children. (5,14) By adjusting for body size however, we have shown that the lower bone size in female CWH, especially in later puberty, is independent of lower height and weight.…”
Section: Discussionsupporting
confidence: 90%
“…Although notably, as found in our study, Canadian CWH in early puberty had higher cortical BMD compared with CWOH. (38) An extensive literature has established a higher prevalence of stunting and underweight in CWH than in CWOH, (4,5,(39)(40)(41)(42) which has been confirmed by our study and our earlier studies in Zimbabwean children. (5,14) By adjusting for body size however, we have shown that the lower bone size in female CWH, especially in later puberty, is independent of lower height and weight.…”
Section: Discussionsupporting
confidence: 90%
“…Each year, over a million children die and develop severe acute malnutrition (SAM), and it presents mainly in marasmus, kwashiorkor, or marasmus kwashiorkor [ 22 , 23 ]. Similarly, in comparison to kwashiorkor, wasting was more commonly reported [ 8 , 24 ], as was early bone growth failure and an increased risk of death in HIV-positive children [ 1 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…SAM among HIV-infected children remains widespread and a serious public health problem in Ethiopia since it is interlinked with different contributing factors [13,21,22].…”
Section: Introductionmentioning
confidence: 99%